Pharmacology for anaesthesia and intensive care - Peck, T. E. 1968-; Harris, Benjamin (Cambridge University Press, 2021)
The fifth edition of this popular textbook continues to provide a solid foundation of pharmacological knowledge for all those working in anaesthesia and intensive care. The content has been thoroughly revised to include expanded chapters with clearer figures, ensuring readers are kept abreast of the ever-changing landscape of clinical pharmacology. Conveniently divided into four sections covering the basic principles of pharmacology, core drugs in anaesthetic practice, cardiovascular drugs, and other important drugs and complemented by new diagrams, tables and chemical formulae to facilitate learning. All four chapters on core drugs in anaesthetic practice have been updated along with others exploring applied pharmacokinetic models, antimicrobials, and drugs used in diabetes. An ideal aid to study and practice for junior and trainee anaesthetists and intensive care specialists preparing for exams. Also an invaluable resource for theatre practitioners, ICU nurses and physicians working in areas that demand a solid knowledge of pharmacology
Title from publisher's bibliographic system (viewed on 26 Feb 2021)
Keywords: Pharmacology; Anesthetics